Foaming and air-water interfacial properties of camel milk proteins compared to bovine milk proteins. (May 2022) - Lajnaf, Roua; Picart-Palmade, Laetitia; Attia, Hamadi; Marchesseau, Sylvie; Ayadi, M.A.
Abstract: The objective of this research was to explore the foaming properties of camel and bovine milk and their derived proteins fractions including sodium caseinates, sweet whey, β-casein, α-lactalbumin and β-lactoglobulin. First, camel and bovine milk proteins were identified by the reversed-phase high-performance liquid chromatography (RP-HPLC) and foaming properties (Foam capacity (FC) and stability (FS)) were analyzed. Afterwards, competitive adsorption of proteins to the air-water interface for both milk protein fractions was characterized using pendant-drop tensiometry parameters and was compared to intrinsic fluorescence results of pure proteins. Experimental results indicated that the maximum FC values were found for camel skim milk, sodium caseinates and β-casein with higher FS values for bovine β-casein. Differences in the stability and the highest tensioactive properties of camel β-casein were explained with the different molecular structure and its higher hydrophobicity when compared to its bovine counterpart. Thus, milk proteins adsorbed layers are mainly affected by the presence of β-casein which is the first adsorbed and the most abundant protein at the air-water contrary to whey proteins (α-lactalbumin and β-lactoglobulin). These globular proteins are involved in the composition of protein layers at air-water interface, giving higher viscoelastic modulus values, but could not compact well at the interface because of their rigid molecular structure. For camel milk, foaming properties and interfacial behavior are mainly maintained by camel β-casein due to its higher hydrophobicity compared to bovine β-casein and the greater exposure of tyrosine residues despite the absence of tryptophan in consistence with the intrinsic fluorescence results. Furthermore, the absence of the β-lactoglobulin leads to the dominance of the α-lactalbumin at the air-water interface which is characterized by lower hydrophobicity than its bovine counterpart leading to lower viscoelastic modulus values than those of bovine whey, and hence to weaker rheological properties of camel milk protein layer at the air-water interface. Graphical abstract: Image 1 Highlights: Foaming and interfacial properties of bovine and camel milk proteins were studied. The α-lactalbumin mainly affects foaming and interfacial properties of camel whey. The absence of β-lactoglobulin in camel milk caused lower stability and film rigidity. Interfacial properties of camel sodium caseinate are dominated by camel β-casein. Camel and bovine β-casein and α-lactalbumin display different fluorescence spectra.